2016
DOI: 10.3847/2041-8205/831/2/l14
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Coherent Pulsations From the Ultraluminous X-Ray Source NGC 7793 P13

Abstract: We report the detection of coherent pulsations from the ultraluminous X-ray source (ULX) NGC 7793P13. The ≈0.42 s nearly sinusoidal pulsations were initially discovered in broadband X-ray observations using XMMNewton and NuSTAR taken in 2016. We subsequently also found pulsations in archival XMM-Newton data taken in 2013 and 2014. The significant (?5σ) detection of coherent pulsations demonstrates that the compact object in P13 is a neutron star, and given the observed peak luminosity of ≈10 40erg s 1 (assumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
378
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(410 citation statements)
references
References 50 publications
18
378
5
Order By: Relevance
“…The energy output rates from ULXs exceed the Eddington limit for accretion onto a 10  M black hole (Feng & Soria 2011), which requires superEddington accretion or intermediate mass black hole accretors Colbert & Mushotzky 1999). Intriguingly, recent observational studies have revealed a population of ULXs that exhibit X-ray pulsations consistent with rapidly rotating and magnetized neutron stars (Bachetti et al 2014;Fürst et al 2016;Israel et al 2016). Accretion onto the neutron star in these ULXs must therefore occur at super-Eddington rates: ULX-1 in NGC 5907 shows peak luminosities of ∼500 times the neutron star Eddington limit (Israel et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The energy output rates from ULXs exceed the Eddington limit for accretion onto a 10  M black hole (Feng & Soria 2011), which requires superEddington accretion or intermediate mass black hole accretors Colbert & Mushotzky 1999). Intriguingly, recent observational studies have revealed a population of ULXs that exhibit X-ray pulsations consistent with rapidly rotating and magnetized neutron stars (Bachetti et al 2014;Fürst et al 2016;Israel et al 2016). Accretion onto the neutron star in these ULXs must therefore occur at super-Eddington rates: ULX-1 in NGC 5907 shows peak luminosities of ∼500 times the neutron star Eddington limit (Israel et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While one or two ULXs may well be intermediate mass BHs (e.g., HLX-1: Farrell et al 2009;Godet et al 2009;Davis et al 2011), the more recent consensus (see Bachetti 2016;Feng & Soria 2011 for reviews, and King et al 2001;Begelman et al 2006;Poutanen et al 2007 for theoretical arguments) is that the vast majority of ULXs are stellar-mass (∼ 10M ) BHs, accreting above their Eddington limit. But not all ULXs are BHs: three objects show coherent pulsations and are thus neutron stars Israel et al 2017Israel et al , 2016Fürst et al 2017Fürst et al , 2016. It is unclear what fraction of ULXs belong to this class (King & Lasota 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the model of Dauser et al (2017) is important because it shows that a slight precession of the outflow can reproduce the nearly sinusoidal pulse profiles observed in the NS pretenders. The shape of the pulse profiles was used in the past to raise objections against strong beaming (Bachetti et al 2014;Brightman et al 2016;Fürst et al 2016, among others), but now it does not appear to be a problem.…”
Section: The Propeller States Of the Three Pretendersmentioning
confidence: 99%
“…(e) Motch et al (2014) determined that the ULX source P13 in NGC 7793 harbors a stellar-mass compact object with M < 15 M ⊙ . Pulsations were next detected from this source (Fürst et al 2016;Israel et al 2017b), so now we know that the compact object is an NS with P S = 0.417 s and an averagė Laycock et al (2015) determined from the radial velocity curve of IC10 X-1 that the compact object could be an NS, although a low-stellar-mass BH cannot be ruled out. (g) Israel et al (2017a) detected pulsations from NGC 5907 ULX-1, so this is the third object of the class harboring an NS with P S = 1.137 s and an averageṖ S = −8.1 × 10 −10 s s −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation